PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA SMA TAMAN MULIA KUBU RAYA - Purwaningsih, Nani; Tampubolon, Budiman; Christanto, Ludovicus Maditya Hari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to determine how much effect the application of problem based learning models on student learning outcomes in learning geography in class XI Taman Mulia Kubu Raya. The research method used was an experimental method, the form of the research was quasy experiment with the nonequivalent control group design. The population in this study were all students of class XI Taman Mulia Kubu Raya, amounting to 61 people. The sampling technique used was probability sampling data collection tool in the form of student learning outcomes tests in the form of objective questions totaling 40 questions. the results of research the average final test of the experimental class was 78.98 and the average final test of the control class was 70.70. Hypothesis test results using the t-test is obtained t_count of 3.71 and ttable with ? = 5% and dk = 59 is 1.9800. Thus tcount> ttable, then Ho is rejected and Ha is accepted. So, it can be concluded that there are differences in student learning outcomes in geography learning between those who apply problem based learning models and those who apply expository learning. The Effect Size obtained ES of 0.87. This means that the problem based learning models has a high effect on the learning outcomes of class XI students at Taman Mulia Kubu Raya.Keywords: Learning Outcomes, Problem Based Learning Models